THE ROLE OF INNOVATIONS AND STARTUPS IN ECONOMIC GROWTH: THE CASE OF UZBEKISTAN - Mashrapov Qudratillo,; Mamadaliyev Jaxongir, (TADQIQOTLAR, 2025)
This  extended  scientific  article  provides  an  in-depth  analysis  of  the  role  of innovations and startups in the economic growth of the Republic of Uzbekistan. The study examines the formation of innovation policy, the stages of startup ecosystem development, and their impact on gross domestic product (GDP), employment, and national  competitiveness  using  statistical  and  analytical  methods.  The  research findings  demonstrate  that  innovations  and  startups  have  become  key  drivers accelerating economic growth in Uzbekistan.